Examining a continuum of FL speaking anxiety over time in an EFL classroom in Japan. (November 2022) - Veenstra, Robert (Jay); Weaver, Christopher
Abstract: Despite the creation of skill-specific measures, the vast majority of researchers interested in foreign language speaking anxiety have relied upon some form of the Foreign Language Classroom Anxiety Scale (Horwitz et al., 1986). In contrast, this study confirmed a continuum of FL speaking anxiety using items from the Public Speaking Class Anxiety Scale (Yaikong & Usaha, 2012) and the Foreign Language Classroom Speaking Anxiety Scale (Apple, 2013). This 18-item continuum was found to be relatively stable over time. Students' perception of six items, however, slightly changed with four items being more likely to elicit anxiety and two items being less likely. This study also found that 341 post-secondary students' overall level of FL speaking anxiety dropped after completing a 15-week required English presentation course. Interestingly, the continuum of FL speaking anxiety revealed that reduced levels of anxiety had different implications depending upon the students' overall level of L2 speaking anxiety. Implications of the study's findings and suggestions for further investigations into FL speaking anxiety within a language classroom are discussed.